Polish-German Bilingualism. Case Study (Activation – innovation – acculturation. (Glotto)didactics and the migration crisis, 2024)
The subject of this article is an analysis of the pronunciation of a bilingual child (Polish-German) who has experienced migration. The aim is to describe how the knowledge of two linguistic repertoires influenced the subject’s pronunciation in terms of the production of Polish sounds. The mispronunciation made by the child were grouped according to Jacek Perlin’s (1995) classification of phonemic interference.